Letter (copy) : Luncheon - McDonald, Florence
012a-0053-001 Secretary's. KMS/852. 3rd September, 1938. Señor Jose I. de Lizaso, 75, Gloucester Terrace, Hyde Park, Dear Sir, LUNCHEON. I am acknowledging receipt of your letter of the 2nd September addressed to Sir Walter Citrine suggesting a luncheon engagement with him. Sir Walter is at present in Blackpool where our Annual Congress is to be held next week, but your letter will be placed before him immediately on his return to London when we will communicate with you again. Yours faithfully. Private Secretary. 292/946/12a/53